Competition Load Described by Objective and Subjective Methods During a Surfing Championship. Issue 5 (May 2018) - FernAndez-Gamboa, Iosu; Yanci, Javier; Granados, Cristina; Freemyer, Bret; Cámara, Jesús
Abstract : Abstract: Fernández-Gamboa, I, Yanci, J, Granados, C, Freemyer, B, and Cámara, J. Competition load described by objective and subjective methods during a surfing championship. J Strength Cond Res 32(5): 1329–1335, 2018—The aims of this study were to describe the competition load of surfers during a single heat through objective and subjective methods and to analyze the relationship between objective and subjective methods with the judges' score. Ten competitive surfers were fitted with a global positioning system (GPS) during a competitive heat. The GPS was synchronized with a chronometer and a stationary video camera to identify the surfer's specific actions. After the end of each heat, participants were assessed for the rating of perceived respiratory and muscular exertion (RPEres, RPEmus), and also, official scores from every participant were collected. A very large significant relationship between wave-riding distance and respiratory perceived exertion heat load (RPEres HL, r = 0.79; ±0.26 confidence limit [CL], p < 0.01, 99.5/0.4/0.1, very likely) was found. Active time was also very large and significantly related to both RPEres HL ( r = 0.75; ±0.29 CL, p < 0.05, 99.0/0.8/0.2, very likely) and muscular perceived exertion heat load (RPEmus HL, r = 0.83; ±0.22 CL, p < 0.01, 99.8/0.2/0.0, most likely). Very large significant correlation was obtained between the RPEres and score ( r = 0.83; ±0.22 CL, p < 0.01, 99.8/0.2/0.0, most likely). The subjective method seems to be a good instrument to assess the HL of a surf competition. Wave characteristics seem to be an important factor in perceived exertion during competitive surfing.